2012
DOI: 10.1002/hyp.9662
|View full text |Cite
|
Sign up to set email alerts
|

Does canopy wetness matter? Evapotranspiration from a subtropical montane cloud forest in Taiwan

Abstract: Evapotranspiration (ET) and canopy wetness were measured over a 2‐year intensive field campaign at the Chi‐Lan Mountain cloud forest site in Taiwan. Eddy covariance and sap flow methods were applied to measure ET and tree sap flow of the endemic yellow cypress (Chamaecyparis obtusa var. formosana). ET was 553 mm yr−1 over the study period with an annual rainfall and fog deposition of 4893 and 288 mm yr–1, respectively. The duration of canopy wetness exceeded actual fog or rain events (mostly in the afternoon),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 86 publications
(172 reference statements)
3
43
0
Order By: Relevance
“…Although R s and VPD were strong drivers of transpiration responses, we also found evidence that leaf wetness suppressed transpiration until a significant threshold of dryness was surpassed. This is important given how frequently leaves were wet in this system, and also suggests that transpiration may be suppressed by leaf wetness in other humid regions (Alvarado‐Barrientos et al, ; Berry, Gotsch, Holwerda, Munoz‐Villers, & Asbjornsen, ; Chu et al, ; Gotsch et al, ; Reinhardt & Smith, ; Ritter, Regalado, & Aschan, ). We observed that transpiration during the two driest months with full records (February and March) was about 26% lower than the two wettest months (July and September, see Figure ).…”
Section: Discussionmentioning
confidence: 86%
“…Although R s and VPD were strong drivers of transpiration responses, we also found evidence that leaf wetness suppressed transpiration until a significant threshold of dryness was surpassed. This is important given how frequently leaves were wet in this system, and also suggests that transpiration may be suppressed by leaf wetness in other humid regions (Alvarado‐Barrientos et al, ; Berry, Gotsch, Holwerda, Munoz‐Villers, & Asbjornsen, ; Chu et al, ; Gotsch et al, ; Reinhardt & Smith, ; Ritter, Regalado, & Aschan, ). We observed that transpiration during the two driest months with full records (February and March) was about 26% lower than the two wettest months (July and September, see Figure ).…”
Section: Discussionmentioning
confidence: 86%
“…Although plants constrain water losses through stomata closure, laurel forest tree species have been previously acknowledged as having low stomatal control and thus follow a profligate water use strategy (González–Rodríguez et al, ; González–Rodríguez et al, ), and this was modelled here via the optimized parameter values of R g 0 and k υ . This feature is also shared by the Sequoia forests in the cloud‐immersed coastline of California and Oregon (Burgess & Dawson, ) and the yellow cypress montane cloud forests in Taiwan (Chu et al, ). For instance, large maximum conductance values up to 300 mmol m ‐2 s ‐1 were maintained for υ of 2–3 kPa in L. novocanariensis (formerly Laurus azorica (Seub.)…”
Section: Resultsmentioning
confidence: 90%
“…and k υ . This feature is also shared by the Sequoia forests in the cloudimmersed coastline of California and Oregon (Burgess & Dawson, 2004) and the yellow cypress montane cloud forests in Taiwan (Chu et al, 2014). the actual T were obtained during summer (Figure 13), a period during which registered fog water collection was higher (Figure 6a,b) and the site was immersed in the cloud bank ( Figure 5), hence the impact of fog disappearance is expected to be greater.…”
Section: Simulation Of Scenariosmentioning
confidence: 86%
See 1 more Smart Citation
“…This also holds true for the cloud forest of Taiwan (Hsieh, 2002). While cloud forest areas of Taiwan are already the subject of intensive research (cf., e.g., Mildenberger et al, 2009;Chu et al, 2012), Taiwan's cloud forest has never been completely mapped on a country-wide scale. The most comprehensive information about the extent of cloud forest in Taiwan available today is given by Li et al (2013), based on the National Vegetation Database of Taiwan.…”
Section: Introductionmentioning
confidence: 99%